A case of camrelizumab-induced anaphylaxis and successful rechallenge: a case report and literature review - Song, Ping; Jin, Yuqi; Dai, Lifang; Fang, Lijun; Tan, Yinuo (Frontiers in Oncology, 2025)
Immune checkpoint inhibitors have been extensively utilized in the treatment of various malignancies, with camrelizumab being one of the agents in this therapeutic class. In this study, we report for the first time a case of an allergic reaction to camrelizumab in a patient with nasopharyngeal carcinoma, who was successfully rechallenged after antiallergic treatment. The patient, a 62-year-old male, was diagnosed with advanced nasopharyngeal carcinoma, exhibiting cancer infiltration and multiple metastases. He underwent multiple cycles of therapy, tolerating camrelizumab, nab-paclitaxel, and nedaplatin (200 mg of camrelizumab every 3 weeks) without adverse reactions in the first four cycles. However, during the fifth cycle, after the intravenous infusion of camrelizumab, he experienced gradual onset of dizziness and chest tightness within 15 minutes (peripheral arterial oxygen saturation was approximately 94%, blood pressure was 76/42 mmHg, heart rate was 83 beats per minute, and respiratory rate was 15 breaths per minute). The camrelizumab infusion was immediately halted, and the patient was treated with intravenous dexamethasone (10 mg) combined with intramuscular diphenhydramine, calcium gluconate, and 500 ml of normal saline; his blood pressure gradually increased to 110/80 mmHg within 10 minutes, and pruritic erythematous macules appeared on his skin, particularly on the upper limbs. Subsequently, nab-paclitaxel was infused, and upon completion, the erythematous macules on the limbs faded. The patient was then rechallenged with a slow infusion of camrelizumab, which was well-tolerated without discomfort or a drop in blood pressure. The patient did not report significant discomfort. Although acute allergic reactions are relatively rare among immune-related adverse events, due to the widespread clinical application of camrelizumab, its potential for allergic reactions should be given high priority.